2013
DOI: 10.1371/journal.pone.0079827
|View full text |Cite|
|
Sign up to set email alerts
|

Application of the UK Foresight Obesity Model in Ireland: The Health and Economic Consequences of Projected Obesity Trends in Ireland

Abstract: BackgroundGiven the scale of the current obesity epidemic and associated health consequences there has been increasing concern about the economic burden placed on society in terms of direct healthcare costs and indirect societal costs. In the Republic of Ireland these costs were estimated at €1.13 billion for 2009. The total direct healthcare costs for six major obesity related conditions (coronary heart disease & stroke, cancer, hypertension, type 2 diabetes and knee osteoarthritis) in the same year were esti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
40
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 69 publications
(44 citation statements)
references
References 12 publications
3
40
0
1
Order By: Relevance
“…The high prevalence of the metabolic syndrome and excessive adipose tissue accumulation (in particular, abdominal obesity) is a major threat to public health, being associated with a substantial decrease in health-related quality of life and an increase in economic costs (1)(2)(3) . Thus, new strategies related to the long-term prevention and reduction of incidence and severity of CVD and type 2 diabetes need to be initiated.…”
mentioning
confidence: 99%
“…The high prevalence of the metabolic syndrome and excessive adipose tissue accumulation (in particular, abdominal obesity) is a major threat to public health, being associated with a substantial decrease in health-related quality of life and an increase in economic costs (1)(2)(3) . Thus, new strategies related to the long-term prevention and reduction of incidence and severity of CVD and type 2 diabetes need to be initiated.…”
mentioning
confidence: 99%
“…Unfortunately, some researchers expect the prevalence for being overweight and obese to reach dramatic levels in the upcoming years. For example, Keaver et al [110] proposed that the overweight and obesity prevalence will reach 89% and 85% in males and females, respectively, by 2030 in Ireland [110]. Wang et al showed that obesity-induced upregulation of miR-24 could function as a feedback regulator of SR-B1 in obesity [61].…”
Section: Sr-b1 and Physical Inactivity/obesitymentioning
confidence: 99%
“…О р и г и н а л ь н ы е р а б о т ы О жирение является независимым фактором риска таких социально-значимых заболеваний, как артериальная гипертензия (АГ), ишемическая болезнь сердца (ИБС), сахарный диабет типа 2 (СД2) [1,2]. Ожирение ухудшает качество жизни, увеличивает расходы на медицинскую помощь [3]. Индекс массы тела (ИМТ) является наиболее часто используемым антропометрическим инструментом для оценки относительного веса и классификации ожирения.…”
Section: ожирение и метаболизмunclassified